Importance of fertilization rates for winter wheat varieties - Uraimov, Izzatbek Abdukhalil ugli (Science and Education, 2024)
The article presents analytical materials based on the results of research to determine the rate of feeding with mineral fertilizers and irrigation of winter wheat “Bardosh” and “Vassa” varieties.